Mobile Applications Available in Germany Supporting Breast Cancer Patients During Treatment and Aftercare: a Systematic Review - Gomm, Susanne Ingrid Marianne; Ebner, Florian K.; Lukac, Stefan; El Taie, Ziad; Janni, Wolfgang; Schmidt-Straßburger, Uta; Stoinschek, Barbara; Dayan, Davut (Geburtshilfe und Frauenheilkunde, 2022)
Purpose Systematic evaluation of health apps designed to support and aid remote monitoring of patients during breast cancer treatment and aftercare.Method A systematic search and assessment of apps was conducted using search terms: breast cancer; breast cancer therapy; and breast cancer aftercare. Evaluation criteria were user assessments, scientifically published benefits, user-friendliness, data protection, app individualization, motivation, and financial aspects. Up to two points (P) could be awarded per criterion. The lowest possible score was 0P and the maximum was 28P. Three examiners from different institutions independently assessed the apps according to the specified criteria. Reference value was defined as the average value given by the examiners. Apps with > 18P were classified as “recommended”; ≥ 11–≤ 18P as “partially recommended” and ≤ 10P as “not recommended”.Results A total of 776 apps (n = 24 from the Apple App Store, n = 752 from the Google Play Store) were identified via search query. After applying exclusion criteria, 36 apps (n = 1 from the Apple App Store; n = 35 from the Google Play Store) were evaluated. Using the mean point values of the examiners, 20 apps were classified as not recommended and 12 as partially recommended (≥ 11–≤ 18P). Four apps were rated partially recommended by two examiners and recommended by one examiner. Three apps were rated as recommended by all examiners.Conclusion Only a small minority of available apps meet recommendation criteria. Use of these apps may benefit breast cancer patients.
Keywords: Brustkrebs; App; Gesundheits-App; Datenschutz; Fernüberwachung von Brustkrebs